Surgical treatment and functional outcome of bilateral symmetrical hip dislocation and Pipkin type II femoral head fracture: a 5-year follow-up case report and literature review - Shakya, Sujan; Chen, Jialei; Xing, Fei; Xiang, Zhou; Duan, Xin (Frontiers in Surgery, 2023)
Abstract Background: Bilateral posterior hip dislocation and femoral head fracture are rare injuries, which may be the earliest case report that focuses on treatment with open reduction via the direct anterior approach (DAA) for bilateral symmetrical Pipkin type II fracture within five years of the follow-up period. Case Report: We present a case of bilateral posterior dislocation with a femoral head fracture (Pipkin II) of the hip in 47 years old woman caused by a high-velocity accident. The dislocation was successfully reduced under general anesthesia at a local hospital and transferred to a tertiary center for surgical management. She was surgically treated with internal fixation using three Herbert screws on the bilateral hips. The direct anterior approach (DAA) was used during surgery. Follow-up for 5 years was performed, and functional outcomes were evaluated using the D’Aubigné range of motion and modified Harris Hip score. The range of motion in the bilateral hip was satisfactory, with no signs of post-traumatic arthritis, heterotopic ossification, or avascular necrosis of the femoral head. Conclusion: Surgical management of bilateral Pipkin type II fractures was performed successfully with open reduction and internal fixation using a safe and reliable direct anterior approach, with good functional outcomes at five- years follow-up.